Human endometrial stem cell-derived small extracellular vesicles enhance neurite outgrowth and peripheral nerve regeneration through activating the PI3K/AKT signaling pathway - Mojdeh Salehi Namini; Nima Beheshtizadeh; Somayeh Ebrahimi-Barough; Jafar Ai (Journal of Translational Medicine)
Abstract Nowadays, extracellular vesicles (EVs) such as exosomes participate in cell-cell communication and gain attention as a new approach for cell-free therapies. Recently, various studies have demonstrated the therapeutic ability of exosomes, while the biological effect of human endometrial stem cell (hEnSC)-derived small EVs such as exosomes is still unclear. Herein, we obtained small EVs from hEnSC and indicated that these small EVs activate the vital cell signaling pathway and progress neurite outgrowth in PC-12 cell lines. For this purpose, hEnSC-derived small EVs were extracted by ultracentrifuge and characterized by DLS, SEM, TEM, and western blot. Also, dil-staining of hEnSC-derived small EVs was done to determine the penetration of hEnSC-derived small EVs into PC12 cells. The MTT assay, scratch assay, and western blot assay were applied to PC12 cells that were exposed to different concentrations of small EVs (0, 50, 100, and 150 µg/ml). Our results demonstrated that small EVs significantly increased neurite outgrowth, proliferation, and migration in PC12 cells in a dose-dependent manner. Moreover, the analysis of western blots showed increased expression of the PI3k/AKT signaling pathway in PC12 cells exposed to hEnSC-derived small EVs in a dose-dependent manner. Also, the results of this study indicated that hEnSC-derived small EVs can enhance cell proliferation and migration and promote neural outgrowth by activating the PI3k/AKT signaling pathway. Accordingly, hEnSC-derived small EVs became an effective strategy for cell-free therapies. Altogether, these positive effects make hEnSC-derived small EVs a new efficient approach in regenerative medicine, especially for the cure of neural injury.